Evaluation of hydrogen-induced cracking in high-strength steel welded joints by acoustic emission technique. (May 2020) - Shiraiwa, Takayuki; Kawate, Miki; Briffod, Fabien; Kasuya, Tadashi; Enoki, Manabu
Abstract: Hydrogen-induced cracking behavior in high-strength steel mainly composed of martensite was analyzed by acoustic emission (AE) technique and finite element method (FEM) in slow strain-rate tensile (SSRT) tests and welding tests. The crack initiation was detected by the AE signals, and the time evolution of stress concentration and hydrogen diffusion were calculated by FEM. The effect of hardness and plastic strain on the hydrogen diffusion coefficient was explicitly introduced into the governing equation in FEM. The criterion and indicator parameter for the crack initiation were derived as a function of maximum principal stress and locally accumulated hydrogen concentration. The results showed that the cracking criterion derived by AE and FEM is useful for predicting the cold cracking behavior and determining the critical preheat temperature to prevent hydrogen-induced cracking. Graphical abstract: Unlabelled Image Highlights: Hydrogen-induced cracking in martensitic high-strength steels Crack initiation criterion was derived by AE and FEM in slow strain rate tests Validity of the derived criterion was assessed in y-grooved welding tests Indicator parameter for hydrogen-induced cracking risk was proposed